Nickel(II)-PPh3 complexes with ONS and ONN chelating thiosemicarbazones: synthesis and inhibition potential on influenza A viruses - TURAN, KADİR (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY-TUBITAK, 2018)
Tetra-coordinated nickel(II) complexes of two ONS (1, 2) and seven ONN (3a-3g) chelating 2-hydroxy-3-methoxy-benzaldehyde thiosemicarbazones were synthesized. The dibasic ligands and complexes bearing PPh3 as a coligand were characterized by means of analytical and spectroscopic data. Cytotoxic activities of the ligands and nickel(II) complexes were determined using the MTT assay in vitro against MDCK cells, and then all the compounds were tested on influenza virus replication by plaque assays. The compounds showed GI(50) values varying from concentrations of 15.9 up to 161.8 mu g/mL for MDCK cells. The plaque assays indicated that one ONS (1) and two ONN (3c and 3d) chelate structures have considerable antiviral effects on influenza A viruses at lower concentrations than the GI(50) values for MDCK cells. The ligands and other complexes did not show any inhibitory effects on influenza virus plaque formation. The effects of the compounds on the influenza virus and structure-antiviral activity relationships were discussed based on the donor atoms and S-alkyl substituents.
Keywords: Thiosemicarbazone; Ni(II) complexes; cytotoxic activity; antiviral; influenza A viruses; PATHOGENIC AVIAN INFLUENZA; NEURAMINIDASE INHIBITORS; STRUCTURAL-ANALYSIS; ANTIVIRAL DRUGS; SOUTHEAST-ASIA; CELLS; HEMAGGLUTININ; BINDING; GLYCOPROTEINS; EPIDEMIOLOGY